Industrial training report: Gamuda Berhad / Nani Atasha Khalid - Khalid, Nani Atasha (Faculty of Business and Management, 2025)
First and foremost, I would like to express my deep gratitude to Allah S.W.T. for His abundant blessings and support throughout my practical training at Gamuda Berhad. Completing my internship has been a remarkable journey, and I firmly believe it would not have been possible without His divine guidance. Secondly, I sincere thank to Universiti Teknologi MARA (UiTM) for giving students like me with the invaluable opportunity to gain exposure to a real working environment. The internship program offered by UiTM has allowed me to apply and enhance the knowledge and skills I acquired during my studies in a practical setting. Then, I would like to thank to Gamuda Berhad for giving me with the great opportunity to learn and grow. This experience has been invaluable to someone like me, who came in with no special expertise. Thank you for believing in my potential and allowing me to develop my skills. I am also profoundly grateful to my supervisors at Gamuda Berhad, especially Ms. Soo Chee Jun, my buddy Noorain Najwa, and the entire Finance Department team. Their guidance, patience, and willingness to share their knowledge have greatly enriched my learning experience. Besides, I would like to express my heartfelt appreciation to my lecturer and advisor, Puan Siti Nurulhuda Binti Ibrahim, for her invaluable guidance and support during my practical training. Her mentorship has been instrumental in helping me understand and apply theoretical concepts in a real-world context. Lastly, I want to thank my family and friends for their unwavering support during my practical training. Their presence and encouragement during challenging times have been a source of strength and motivation.